Gangguan Ginjal Akut et Kausa Sepsis: Laporan Kasus - Kairupan, Jaquelene D.; Palar, Stella (Universitas Sam Ratulangi, 2020)
Abstract: Acute kidney injury (AKI) is a sudden episode of decreased renal function that occurs within a few hours until a few weeks, followed by renal failure in excretion of nitrogen-waste products with or without imbalance of fluid and electrolytes. Sepsis is the main cause of critical illnesses as well as the main cause of AKI, albeit, the pathophysiology of AKI due to sepsis is not jet fully understood. We reported a female patient aged 35 years with AKI due to sepsis caused by abscess of suprafundal uterine that occured due to nosocomial infection post laparoscopy of utero myoma. Diagnosis was based on anamnesis, physical examination, and laboratory examination as well as radiology examination. The patient had been given an adequate antibiotic treatment with infection source control, renal supportive therapy using intermittent hemodialysis, exploration surgery, and abscess drainage. The prognosis of this patient was good since the condition of sepsis was resolved and the renal supportive therapy of hemodialysis improved her renal function.Keywords: acute kidney injury, sepsisÂ Abstrak: Gangguan ginjal akut (GgGA) adalah penurunan fungsi ginjal yang terjadi mendadak dalam beberapa jam sampai beberapa minggu, diikuti oleh kegagalan ginjal untuk mengekskresi sisa metabolisme nitrogen dengan atau tanpa disertai terjadinya gangguan keseimbangan cairan dan elektrolit. Sepsis merupakan penyebab utama dari penyakit kritis dan juga merupakan faktor penyebab paling umum untuk terjadinya GgGA namun patofisiologi terjadinya GgGA akibat sepsis belum dipahami dengan jelas. Kami melaporkan seorang pasien wanita usia 35 tahun dengan GgGA akibat sepsis yang disebabkan oleh abses suprafundus uteri dengan kausa infeksi nosokomial pasca laparoskopi mioma uteri. Diagnosis ditegakkan berdasarkan anamnesis, pemeriksaan fisik, pemeriksaan laboratorium dan radiologi. Pasien telah diberikan pengobatan antibiotik adekuat dengan kontrol sumber infeksi, terapi suportif ginjal menggunakan intermittent hemodialysis, operasi eksplorasi, dan drainase abses. Prognosis pada pasien ini ialah baik bila kondisi sepsis teratasi dan terapi suportif ginjal hemodialisis memberi hasil perbaikan fungsi ginjal.Kata kunci: gangguan ginjal akut (GgGA), sepsisÂ